2019
DOI: 10.1016/j.jdeveco.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

School feeding and learning achievement: Evidence from India's midday meal program

Abstract: We study the effect of the world's largest school feeding program on children's learning outcomes. Staggered implementation across different states of a 2001 Indian Supreme Court Directive mandating the introduction of free school lunches in public primary schools generates plausibly exogenous variation in program exposure across different birth cohorts. We exploit this to estimate the effect of program exposure on math and reading test scores of primary school-aged children. We find that midday meals have a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 34 publications
3
43
1
1
Order By: Relevance
“…A midday-meal is also provided in preschool centres as part of early childhood support. Recent evidence has demonstrated the programme's positive impact on learning (Chakraborty & Jayaraman, 2016) and on mitigating the effects of early shocks on preschool nutritional status (A. Singh, Park, & Dercon, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A midday-meal is also provided in preschool centres as part of early childhood support. Recent evidence has demonstrated the programme's positive impact on learning (Chakraborty & Jayaraman, 2016) and on mitigating the effects of early shocks on preschool nutritional status (A. Singh, Park, & Dercon, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Performance evaluation of the program reported increase in school enrolment, decrease in pupil and teacher absenteeism and improvement of health among primary school children. A recent study [28] examining the nutrition-learning link in the program showed increase in standardized test scores for reading and mathematics. In comparison, the present study showed evidence of the association between nutritional status and mean school grades, although the improved status could have been sustained to the household level.…”
Section: Discussionmentioning
confidence: 99%
“…On average, healthy children have better educational outcomes than unhealthy children, and this educational advantage translates to higher earnings over their lifetime 78921. Experiments around the world found significantly higher maths and language scores and attendance rates in schools that operated a school feeding programme compared with schools that did not 2223242526. A randomised trial in a region of India with widespread iron deficiency anaemia found that maths and language scores were higher among children who regularly participated in a school feeding programme that included salt fortified with iron 27.…”
Section: Effects Of Childhood Dietsmentioning
confidence: 99%